Matthew’s Discourse on Brotherly correction (Matt 18:15-17) as a model of Conflict Resolution in traditional Communities: The case of Igbo Umunna - Onyenali, Rowland (Biblical theology bulletin, 2025)
Conflict is an essential part of human existence. It manifests itself where people or things struggle for scarce values. Conflict brings about breakage in interpersonal relationships and divides communities. The pericope of Matthew’s gospel (18:15–17) is concerned with the running of a Christian community and the discipline of its members. Its special focus is the resolution of conflicts among members of the community. The verses recommend a process of reconciliation and forgiveness of offences that involves several stages. Central to the issue at stake is the injunction that a believer who sins against a brother and refuses to listen to the brother, to the witnesses and to the community (ecclesia) is to be treated as a tax collector or as a gentile. This paper studies this gospel idea in relationship with the reconciliatory process of the traditional Igbo Umunna (community). It argues that the Igbo community plays a vital role in conflict resolution to bring back erring brothers to the community just as Matthew’s Jesus showed concern for the resolution of conflicts in the community of his followers.